Interpretasi As-Sukhriyyah, Al-Lamz, dan At-Tanabuz bi al-Alqab dalam QS Al-Hujurat [49]: 11: Studi Tafsir Al-Misbah dan Relevansinya terhadap Kekerasan Verbal - Fara Aprillia Puteri; Nurliana Damanik (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study examines M. Quraish Shihab’s interpretation of three communication prohibitions in QS. Al-Hujurat [49]: 11—as-sukhriyah, al-lamz, and at-tanābuz bil-alqāb—and their relevance to contemporary verbal violence. It focuses on the conceptual relationship among the three prohibitions in Tafsir Al-Misbah and their contribution to Islamic communication ethics. This qualitative library research uses the Qur’an and Tafsir Al-Misbah as primary sources, supported by exegetical works, Arabic dictionaries, books, journal articles, and other relevant literature. Data were analyzed using qualitative content analysis through identification, categorization, interpretation, and conclusion drawing. The findings show that as-sukhriyah, al-lamz, and at-tanābuz bil-alqāb are not separate prohibitions but form an integrated communication ethics oriented toward preserving human dignity (hifz al-‘irḍ), strengthening ukhuwah, and preventing various forms of humiliation. The main root of these prohibitions is a sense of superiority over others. This interpretation is relevant for reading contemporary verbal violence such as cyberbullying, body shaming, hate speech, and derogatory nicknames in digital media. Therefore, QS. Al-Hujurat [49]: 11 can serve as a normative foundation for building respectful, ethical, and dignified communication culture.